A Report on GIS Based Analysis of Landslides in Myagdi District - Thapa, Sumit (Journal of the Institute of Engineering, 2021)
Lanslide have become a routine event during monsoon in Nepal which accompanies a huge social, physical and economical loss. As the number of landslide event is in increasing order each year but their proper study is still limited, this assessment is an example of simple step in landslide study. Also, the developmental activities disturb the topology and hence increase or bring new form of landslide in the region. This report is mainly a preliminary study of existing landslide in Myagdi district which is generally carried out using QGIS software and remote sensing data available from http://earthexplorer.usgs.gov and recent Google satellite image. From the analysis carried out by using the inbuilt features in QGIS, relationship between various terrain, hydrological and anthropogenic parameters with landslide was driven. Based on this approach a simple precautionary measures in development activities, disaster preparedness and mitigation activities can be carried out.